Effect of maturation on the relationship between muscle size and force production - Tonson, A.; Ratel, S.; le Fur, Y.; Cozzone, P.; Bendahan, D. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Although it is well accepted that an increase in muscle size is linked to an increase in muscle force, the relationship between muscle size and maximal strength during maturation is still discussed. In the present study we aimed at determining whether maturation affects the relationship between muscle size and maximal strength, and we investigated the reasons accounting for the discrepancies among previous studies.